İki değerli demir sülfattan y-Fe2O3 sentezi ve karakterizasyonu - Sesigür, M. Hakan (Fen Bilimleri Enstitüsü, 1996)
Bu çalışmada Ereğli Demir Çelik Fabrikaları Pickling Banyosu artıkları (FeSO^EMD) kullanılarak manyetik bant teknolojisinde kullanılan y-Fe203 üretiminin parametreleri incelenmiştir. Camras Patentine uygun olarak çekirdekleştirici ürün eldesine yönelik çalışmada 17 saat reaksiyon sonucunda 35 nr.g"1 yüzey alanına sahip ve asiküler oksit üretimine elverişli ara ürün elde edilmiştir. Elde edilen çekirdekleştirici ürün üzerinde götit tanesinin büyütülmesine yönelik çalışmada optimum şartlar 60°C ve 300 dev.dak"1 karıştırma hızında, 50 g.l"1 FeS04.7H20 başlangıç konsantrasyonu 450 l.s"1 hava üfleme debisi ve 3 numara firitten sağlanan hava kabarcıkları olarak saptanmış ve bu şartlarda yapılan deneylerden alınan ürün üzerinde standart şartlarda yapılan işlemlerden sonra elde edilen üründe 28.3 nr.g"1 spesifik yüzey alanı, 240 Oe koersivite değeri ve 103.7 emu.g"1 manyetik doymuşluk elde edilmiştir. Götit tanelerinin dehidratasyonunda en uygun sıcaklık 250°C ve süre 30 dakika olarak saptanmıştır. Daha sonra yapılan redüksiyon işleminde uygun sıcaklık 380°C ve 15 dakikalık reaksiyon süresi olarak bulunmuştur. Bundan daha düşük sıcaklık ve sürelerde yapdan deneylerde yapıda kalıntı hematit' e rastlanmıştır. Buna karşılık daha yükse sıcaklık ve deney sürelerinde ise yapıda metalik demire raslanmışür. Nihai ürün olan y-Fe2(V in üretimindeki son aşama olan reoksidasyon işleminde en uygun sıcaklık 220°C ve süre 10-15 saat arası olarak bulunmuştur. Artan sıcaklık ile kalıntı Fe "*' in azalmasına karşılık koersivite değerinin düştüğü saptanmıştır. Artan süre ile ise hem Fef+ miktarı azalmakta hem de koersivite artmaktadır. Yukarıda belitreilen optimum şartlarda üretilen manyetik demir oksit, 28.3 nr.g"1 spesifik yüzey alanına sahip asiküler (boy/çap = 7.6) yapıda ve 350-380 Oe koersiviteye sahiptir.

Magnetic recording was invented by POULSEN ( 1900 ), who demonstrated that electrical signals could be written on to an iron wire which was wrapped around a drum. Stainless steel wire was used in later recorders, but in the 1940's recording surfaces composed of the particles of iron oxide, at first on paper substrates and later on plastic films, gained oscendancy. Magnetic recording finds continually increasing application in audio, video, instrumentation and computers,and now accounts for the largest amount of money spent on magnetic products. There are several reasons for it cs popularity as a means of information storage, in addition to it's economy,fidelity and reliability. First it is simple to use : No development step is needed between the writing and reading processes and hence one can go back at any time and add to an in complete record : that is it is passable. Second information is stored as a passive condition of the medium ; It does not need to be regenerated continuously ; it is nonvolatile Third, the stored information is usually quite unaffected by the environment, such as changes in temperature or pressure,or the presence of ionizing radiation or electric or magnetic fields (smaller than the coercivity of the medium ). Finally,the information can be erased and the same surface used to make another recording, the process is apparently infinitely reversible. From the begging of the sudden growth in popularity of magnetic recording (c.1945) to the present,one magnetic material as dominated the technology; that material is y-Fe203 in the from of small acicular single-domain particles. As more than 99 % of commercially available tapes and discs make use of y-Fe^ particles. The starting material from which acicular particles of the iron oxides are prepared is alpha ferric oxyhyroxide ( a (FeO) OH ) =synthetic geothite ), which can be obtained in acicular crystalline from. This is available commercially as a yellow pigment, or it can be made by a process described by Penniman and Zoph (1921) and later, in more detail, by CAMRAS (1954 ) Sodium hydroxide solution and ferrous sulfate solution are agitated so that afresh surface is continually exposed to the atmosphere and oc.( FeO ) OH is precipitated in colloidal from : 4FeS04 7H20 + 02 + 8NaOH -» 4 a-(FeO) OH + 4H2S04 + 30 H20 VII The colloidal particles are next used as nuclei in growth of larger crystals of a - (FeO )OH. More ferrous sulfate is mixed with water and scrap iron and heated to 60 °C and then the seed material produced in the step described above is added and air bubble through the mixture for about four hours. During this time a.(FeO) OH grows on the colloidal nuclei to produce light. yellow acicular crystals. The sulfuric acid formed in the process produces more ferrous sulfate by reacting with the iron The crystals of a.(FeO) OH are then filtrated washed and dried and are seen in the electron microscope to be 0.25-1. 5um long and 0. l-0.3um wide. The yellow acicular crystals of a (FeO )OH are dehydrated at 230 - 270 °C to give red acicular crystals of hematite : 2 a - (FeO ) OH -> a-Fe203 + H2 O which are then reduced by heating in hydrogen at 300 -400 °C to black acicular crystals of magnetite 3a - Fe203 + H2 -> 2Fe304 +H20 although van Oesterhout (1965 ) believes that the iron oxide at this stage contains excess Fe203 the last step is the reoxidation of the magnetite particles at about 250 °C given the reddish -brown acicular particles of y - Fe203.There is no appreciable change of shape or size of the particles in the series of steps represented by Pigment -» dehydrated oxide -» magnetite -> maghemite a-(FeO)OH cc-Fe^ Fe304 y-Fe203 The production steps of y -Fe203 are summerized in Figure 1. Inthis study, the synthesis of y -Fe203 which can be used in magnetic audio, video and data storage, from iron salts (FeS04.7H20) which was obtained by crystallization of iron and steel pickling baths was investigated. The impurity analysis of FeS04 7H20 obtained from Ereğli Iron & Steel Company is given in Table 1 via NaOH FeS04.7H20 Air FeSO^ 7H20 Scrap Fe 'Seed Material' Preparation Seed Material Geothite Precipitation Discarded Solution H-,0 H,0 Air a -FeiOi I Reduction Re-Oxidation i y-FeoO^ Figure 1. The flow sheet for the synthesis of y-Fe20? IX Table I. The impurity Analisis of FeS(>4 7H20 This study can be classified in to 5 groups; ( 1 ) preparation of "seed material" (2) precipitation of geothite (3) dehydratation (4) reduction (5) reoxidation The first experimental concucted research was the preparation of geothite nuclei which is an initial material for y-Fe^C^ in acicular shape. The nuclei produced by adding NaOH in stochiometric amounts in to FeSC>4.7H2O which was dissolved in water, become available for synthesis of acicular y-Fe^Oj after having a specific surface area of 35m2g~l during 17 hrs of reaction time. The optimal conditions for enlarging acicular geothite grains on produced nuclei are; FeS04 7H20 concentration 50 g.l"1, temperature 60°C, stirring rate of 300 rpm., and 4501. h"1 air rate purged through a frit which has pores of 16-40 urn. In diameter (number 3). The geothite produced under these conditions have a specific surface area of 28-30 irf.g"1. For the dehydratation of acicular geothite to a -Fe^O?, temperature of 250°C and decomposition time of 30 minutes is adequate. In the process of a -Fe^O? to FesC^ with hidrogen, the optimum conditions are 380°C and 15 minutes. Lower temperatures and shorter times result in insufficient reduction however higher temperatures and longer times result in excessive reduction and couse the reduction to metallic iron. The transformation of metastable Fe3C>4 to y -Fei03 was carried out in air via reoxidation. The most appropriate conditions for reoxidation are 220°C and 10-15 hours. At lower temperatures and shorter times, the amount of Fe ^ remained in the structure is high which indicates insufficient transformation. Although the amount of Fe~ decreasses below 0.5% at higher temperatures and longer times, a decrease was observed in coercivity values which is due to the transformation of the structure from y to a -Fe^Os. The y -Fe^Os synthesized under the optimum conditions given above is a magnetic material in acicular shape (l/d=7-8), has a specific surface area of 28-30 nr.g"1 and has a coercivity of 350-380 Oe.
Tez (Doktora)-- İTÜ Fen Bil. Enst., 1996.
Keywords: Demir oksit; Demir sülfat; Iron oxide; Ferrous sulphate